Congenital Adrenal Hyperplasia (Case Report) - Marwoto Marwoto; Achmad Surjono (Paediatrica Indonesiana, 1976)
A case of a female infant with congenital abnormality of the urogenital apparatus, an excess of the urinary 17-ketosteroid, mild salt losing disorder, acceleration of growth ossification, described as congenital adrenal hyperplasia due to 21-hydroxylase defect has been reported.